Medical Sociology and Social Theories of Health and Disease (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The relationship of sociology with medical knowledge from the beginning was notan easy task between two different scientific fields to produce knowledge ofdisease, health and health care. Rather, sociological intervention in the field ofmedicine was not acceptable by specialists in the medical field. However, with thedevelopment of social life and overlapping multiple factors in the emergence ofdiseases, their diagnosis and methods of treatment, the gradual opening ofmedicine to sociology appeared in an attempt to introduce some social factors inthe interpretation of diseases, the role of the patient, the relationship between thedoctor and the patient, and the formulation of some scientific approaches andtheories.